The AMPK-like protein kinases Sik2 and Sik3 interact with Hipk and induce synergistic tumorigenesis in a Drosophila cancer model - Yu, Kewei; Ramkumar, Niveditha; Wong, Kenneth Kin Lam; Tettweiler, Gritta; Verheyen, Esther M. (Frontiers in Cell and Developmental Biology, 2023)
Homeodomain-interacting protein kinases (Hipks) regulate cell proliferation, apoptosis, and tissue development. Overexpression of Hipk in Drosophila causes tumorigenic phenotypes in larval imaginal discs. We find that depletion of Salt-inducible kinases Sik2 or Sik3 can suppress Hipk-induced overgrowth. Furthermore, co-expression of constitutively active forms of Sik2 or Sik3 with Hipk caused significant tissue hyperplasia and tissue distortion, indicating that both Sik2 and Sik3 can synergize with Hipk to promote tumorous phenotypes, accompanied by elevated dMyc, Armadillo/β-catenin, and the Yorkie target gene expanded. Larvae expressing these hyperplastic growths also display an extended larval phase, characteristic of other Drosophila tumour models. Examination of total protein levels from fly tissues showed that Hipk proteins were reduced when Siks were depleted through RNAi, suggesting that Siks may regulate Hipk protein stability and/or activity. Conversely, expression of constitutively active Siks with Hipk leads to increased Hipk protein levels. Furthermore, Hipk can interact with Sik2 and Sik3 by co-immunoprecipitation. Co-expression of both proteins leads to a mobility shift of Hipk protein, suggesting it is post-translationally modified. In summary, our research demonstrates a novel function of Siks in synergizing with Hipk to promote tumour growth.